KEEFEKTIFAN PEMBELAJARAN TEKS NARASI YANG MENGGUNAKAN CERITA RAKYAT TIMOR - Rince Jalla Wabang; Metropoly M.J. Liubana; Maria Rosalinda Talan (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The aim of the current study was to delineate the efficacy of teaching narrative texts by using Timorese folklore as teaching material. The subjects in this study were seventh-grade students of SMPN Noemuti. The data procurement technique comprised observation, questionnaire, and test. Observation was carried out to find out the activities of students, a questionnaire was conducted to figure out the students' responses regarding the integration of Timorese folklore in learning, and a test was undertaken to find out the students’ learning outcomes. The result of the study revealed that in learning narrative texts using Timorese folklore, students’ activity reached 82% in the very good category, student learning outcomes achieved an average score of 81,5 which categorized as very good, teacher and student responses reached 97,2% which was categorized as very good. Thus, it was concluded that Timorese folklore was very effectively applied in teaching narrative texts to seventh-grade students of SMP Negeri Noemuti.